Pengaruh Penggunaan QRIS Sebagai Metode Pembayaran Terhadap Perilaku Konsumtif Mahasiswa di Yogyakarta - Anastasya Amanda Putri; Agista Riani Riswanmudib; , Hanif Luqman Naufal (CV. ITTC INDONESIA, 2025)
The transformation of the payment system in Indonesia has experienced quite rapid development. The presence of QRIS as a payment method has brought changes to the way people transact. This study aims to find out whether QRIS affects the consumptive behavior of students in Yogyakarta. The method used in this study is quantitative, with data collection techniques through the distribution of questionnaires. The data obtained was then tested using the SPSS application to identify the influence between the two variables. From this study, the results were obtained that QRIS affected the consumptive behavior of students in Yogyakarta by 37.5%, while the remaining 62.5% was influenced by other variables that were not included in the research object.